Efek Jera Pemidanaan Dalam Hukum Islam dan Penerapannya di Indonesia - Kadir, Muh. Awaluddin; Shuhufi, Muh; M, Misbahuddin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The journey of the implementation of Islamic criminal punishment in Indonesia has  experienced a long discussion, especially in terms of human rights violations. The deterrent effect of punishment in the context of Islamic law can be seen from the sanctioning of criminals. This research aims to: First: to reveal the deterrent effect in the criminal system of Islamic law and compare it with the legal system in Indonesia. Second: Measuring the opportunity of applying Islamic law in providing a deterrent effect for criminal offenders in Indonesia. The type of research that will be used in this research is library research (lybrary research). Library research is a type of research that uses data sources from literature or written materials in libraries or online databases. Punishment in Islamic law is a set of laws that emphasize providing a deterrent effect on criminals so as to prevent future crimes. The results of the study prove that the application of Islamic law in providing a deterrent effect for perpetrators of criminal acts in Indonesia. This is because Islamic law is one of the sources of law in Indonesia. The application of Islamic law can be achieved if the legislature agrees to enforce Islamic law in Indonesia.